Culture and anarchy - Arnold, Matthew, 1822-1888 (Oxford world's classics (Oxford University Press), 2006)
First published in 1869, Culture and Anarchy debates questions about the nature of culture and society. Arnold asks what good culture can do and how it can best be disseminated. This edition reproduces the first book version and enables readers to appreciate its historical context and its continued importance. - ;'The men of culture are the true apostles of equality.'. Matthew Arnold's famous series of essays, which were first published in book form under the title Culture and Anarchy in 1869, debate important questions about the nature of culture and society that are as relevant now as they h.